Interdisciplinary approach to the management of patients with uterine cancer progression - K. Yu. Morkhov; Yu. M. Kreinina; I. A. Pokataev; V. M. Nechushkina (Опухоли женской репродуктивной системы)
Endometrial cancer is the most common gynecologic malignancy in Russia. Surgery and/or chemoand radiotherapy remain standard clinical approach. This review describes multidisciplinary approach as the state of the art in the disease management. We notice the importance of molecular assessment for driving the clinic decision and newly emerging medical treatments, such as immunotherapy and antiangiogenic tyrosine kinase inhibitors and immunotherapy combinations.